Free Triiodothyronine Is Associated With Hepatic Steatosis and Liver Stiffness in Euthyroid Chinese Adults With Non-Alcoholic Fatty Liver Disease - Guo, Wen; Qin, Pei; Li, Xiao-Na; Wu, Juan; Lu, Jing; Zhu, Wen-Fang; Diao, Qing-qing; Xu, Nian-Zhen; Zhang, Qun (Frontiers in Endocrinology, 2021)
Objective The association between non-alcoholic fatty liver disease (NAFLD) and thyroid hormones in euthyroid subjects is unclear. We investigated the relationship between thyroid function and the severity of hepatic steatosis and liver fibrosis in a large cohort of euthyroid Chinese adults. Methods A total of 3496 participants were enrolled. Liver ultrasonography was used to define the presence of NAFLD (n=2172) or the absence of NAFLD (n=1324). Anthropometric and biochemical measurements were made and thyroid function parameters including free triiodothyronine (FT3), free thyroxine (FT4), thyroid‐stimulating hormone (TSH) were measured. The severity of hepatic steatosis and liver stiffness was assessed by transient elastography. Results Levels of FT3 were significantly higher in the severe NAFLD group and moderate NAFLD group than in the mild NAFLD group (5.18 ± 0.58 vs 5.11 ± 0.57 vs 4.98 ± 0.60 pmol/L, P<0.001). Participants with F4 and F3 liver fibrosis had higher FT3 levels than those with F2 fibrosis (6.33 ± 0.39 vs 5.29 ± 0.48 vs 5.20 ± 0.50 pmol/L, P<0.001). However, FT4 and TSH levels did not correlate with hepatic steatosis or liver fibrosis severity. In addition, the proportions of participants with NAFLD (46.0% vs 63.1% vs 73.3%, P<0.001) and liver fibrosis (11.5% vs 18.6% vs 20.8%, P<0.001) increased as FT3 levels increased. Logistic regression analysis showed that FT3 levels were positively associated with the severity of hepatic steatosis and liver fibrosis presence, even after adjustment for metabolic risk factors including BMI. In non-obese participants, the FT3 level was an independently risk factor for the severity of hepatic steatosis. Conclusions There are positive associations of FT3 levels with the severity of hepatic steatosis and the presence of liver fibrosis in NAFLD with euthyroidism.